Preparation method of toughened bismaleimide resin

The synergistic reaction of diamine and bismaleimide and the synergistic action of diallyl bisphenol is formed, which solves the problem of insufficient toughness of traditional bismaleimide resins and significantly improves its Mechanical and thermal properties, suitable for aerospace.

CN119285950APending Publication Date: 2025-01-10SHANDONG NON METALLIC MATERIAL RESEARCH INSTITUTE
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411634982.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Traditional bismaleimide resins have limited their application in the aerospace field due to their poor toughness, especially due to their symmetrical molecular structure and high crosslinking density, resulting in insufficient toughness of cured substances.

Method used

The chain extension of the diamine toughening agent and bismaleimide is formed by reacting a diamine toughening agent and extending the chain, and reacting in concert with diallyl bisphenol to form a prepolymer B to enhance the toughness of the resin. Reaction and step-by-step temperature-raising curing processes, controlling molar ratio and prepolymerization temperature to optimize the mechanical and thermal properties of the resin.

Benefits of technology

It significantly improves the toughness and thermal properties of bismaleimide resin, improves processability, extends molding time, reduces system viscosity, enhances mechanical properties and thermal stability, and is suitable for aerospace fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285950A_ABST
    Figure CN119285950A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of resin modification research, and particularly relates to a preparation method of toughened bismaleimide resin. The preparation method comprises the following steps: pre-polymerizing a diamine toughening agent and bismaleimide resin to form a prepolymer A, blending the bismaleimide resin by virtue of the prepolymer A and diallyl bisphenol a with different contents, and curing the blended resin by adopting a specific process after blending, so as to obtain the toughened bismaleimide resin cured product. The toughened bismaleimide resin cured product prepared by the invention has excellent toughness and heat resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resin modification research, and specifically relates to a preparation method of toughened bismaleimide resin. Background Art

[0002] Advanced resin-based composite materials are a new type of material that is made of organic polymer materials as a matrix and high-performance fibers as reinforcements through a certain process. They have significantly better performance than the original components. APC has the characteristics of light weight, high strength, high modulus, and strong fatigue resistance. The amount of APC has become an important indicator for judging the degree of advancement of aircraft. It is the fourth largest aviation structural material after titanium alloy, aluminum alloy, and steel. In addition, APC is also widely used in automobiles, ships, power generation and other fields. At present, the main APC resin matrices are epoxy resin (EP), bismaleimide resin (BMI), polyimide resin (PI), etc. Among them, bismaleimide resin has the excellent processing performance of epoxy resin and the excellent heat resistance of polyimide resin, and has attracted more and more attention from researchers in recent years.

[0003] Bismaleimide (BMI) is a class of excellent bifunctional compounds terminated by two maleimide (MI) groups, and its comprehensive performance is between that of polyimide resin and epoxy resin. Generally, BMI has a symmetrical molecular structure and contains a large number of rigid structures, so BMI has excellent heat resistance. The thermal decomposition temperature of most BMI resins is greater than 450°C. It also has good processing performance, low moisture absorption rate, radiation resistance and other characteristics, and is widely used in the aerospace field. Due to the high polarity and symmetrical structure of BMI molecules, its solubility is poor. It is difficult to dissolve in common solvents such as dichloromethane, ethanol, and acetone, but can be dissolved in high boiling point, highly toxic, and highly polar organic solvents such as DMF.

[0004] Traditional bismaleimide has a short molecular chain, symmetrical structure and contains more rigid groups. It has a high crosslinking density after curing. This molecular structure gives it excellent heat resistance but also leads to poor toughness. Unmodified bismaleimide resin has disadvantages such as poor toughness of cured products, high melting point and poor solubility. Among them, poor toughness is the biggest reason limiting its use. It is necessary to toughen bismaleimide resin on the basis of ensuring its excellent heat resistance. Summary of the invention

[0005] Based on the problem of poor toughness of bismaleimide, the present invention provides a method for preparing a toughened bismaleimide resin. In the present invention, a prepolymer A is obtained by chain extension through reaction of a diamine toughening agent with bismaleimide, and then the prepolymer A and diallyl bisphenol A are used to synergistically toughen and modify the bismaleimide resin, thereby solving the disadvantage of poor toughness of the bismaleimide resin and obtaining a modified resin with excellent mechanical properties and thermal properties, which may be further applied in the field of aerospace.

[0006] To achieve the above purpose, the specific technical solution of the present invention is as follows:

[0007] A method for preparing a toughened bismaleimide resin, comprising the steps of:

[0008] (1) A diamine toughening agent and diphenylmethane bismaleimide are mixed in proportion and reacted in a molten state to form a prepolymer A (a binary prepolymer of diamine and diphenylmethane bismaleimide).

[0009] (2) Prepolymer A, diallyl bisphenol A and diphenylmethane bismaleimide are reacted in a molten state to form prepolymer B.

[0010] (3) The prepolymer B is poured into a mold and cured at high temperature to obtain a bismaleimide resin with good toughness and heat resistance.

[0011] Preferably, the molar ratio of the diamine toughening agent to the diphenylmethane bismaleimide in step (1) is 1: (1-2), more preferably 1: 2. If the molar ratio of the diamine to the bismaleimide is too large, the heat resistance loss will be too large; if the molar ratio of the diamine to the bismaleimide is too small, the toughening effect will not be obvious, so the molar ratio is controlled to be 1: (1-2).

[0012] Preferably, the prepolymerization temperature in step (1) is 130-180°C, more preferably 180°C; the prepolymerization time is 10-30 min, more preferably 20 min. If the prepolymerization temperature is too high or the time is too long, the resin will solidify too quickly and the viscosity will increase sharply; if the prepolymerization temperature is too low or the time is too short, the prepolymerization degree will be insufficient.

[0013] Preferably, in step (2), the molar ratio of diphenylmethane bismaleimide to diallyl bisphenol A is 1:(0.8-1), more preferably 1:0.8.

[0014] Preferably, the amount of prepolymer A added in step (2) is 3-18% (mass fraction) of prepolymer B, more preferably 3-15%, most preferably 3-9%. Too high a content of prepolymer A will result in excessive viscosity of the system during the casting process, increasing the difficulty of handling.

[0015] Preferably, the prepolymerization temperature in step (2) is 130-150°C, more preferably 140°C; the prepolymerization time is 0.5-1h, more preferably 1h. If the prepolymerization temperature is too high or the time is too long, the resin will solidify too quickly and the viscosity will increase sharply; if the prepolymerization temperature is too low or the time is too short, the prepolymerization degree will be insufficient.

[0016] Preferably, in step (3), the prepolymer B is poured into the mold and then vacuum degassed for 0.5-1 h.

[0017] Preferably, the curing in step (3) adopts a step-by-step temperature-increasing curing process, and the specific curing process is 150° C., 1 h→180° C., 2 h→210° C., 4 h→230° C., 4 h.

[0018] The diamine toughening agent contains a naphthalene ring and an ether bond structure, and its molecular structure is shown in Formula I:

[0019]

[0020] The molecular structure of diallyl bisphenol A is shown in Formula II:

[0021]

[0022] The preparation method of the diamine toughening agent described in the present invention is not limited, and can be prepared by using existing technology, for example, reference can be made to the literature (Polymer Materials Science and Engineering, 2011, 27(11), 1-3). Specifically, it can also be prepared according to the following steps:

[0023] 1) In N,N-dimethylformamide, 2,7-dihydroxynaphthalene, p-nitrochlorobenzene and anhydrous potassium carbonate are reacted at 120-150°C for 6-12h. After the reaction is completed, the mixture is filtered while hot. After the filtrate is cooled to room temperature, a large amount of crystals are precipitated. The crystals are then filtered and retained. The crystals are washed with water for multiple times and then dried in an oven to obtain a dinitro compound.

[0024] 2) The obtained dinitro compound is reacted at 75-105°C for 8-10h under N2 atmosphere, with ethylene glycol methyl ether as solvent, hydrazine hydrate as reducing agent, activated carbon as adsorbent and FeCl3˙6H2O as catalyst. After the reaction, the reaction is filtered while hot. After the filtrate is cooled to room temperature, a large amount of crystals are precipitated. The precipitated crystals are washed with water for several times and then dried to obtain a diamine toughening agent.

[0025] Preferably, the reaction temperature in step 1) is 150°C.

[0026] Preferably, the reaction time in step 1) is 10 h.

[0027] Preferably, the reaction temperature in step 2) is 100°C.

[0028] Preferably, the reaction time in step 2) is 8 h.

[0029] In step 1), the structural formulas of 2,7-dihydroxynaphthalene, p-nitrochlorobenzene and dinitro compound are shown in formula III, formula IV and formula V respectively.

[0030]

[0031]

[0032] Compared with the prior art, the technical effects of the present invention are:

[0033] (1) Compared with the diamine tougheners (DDM, DDS, etc.) of traditional bismaleimide resins, the diamine tougheners in the present invention have longer molecular chains and contain flexible ether bonds, which can increase the spin of the molecular chain and further toughen it. At the same time, the naphthalene ring is a rigid group, which can make up for the reduced heat resistance caused by the longer molecular chain and the introduction of the ether bond. The diamine can react with bismaleimide to undergo Michael addition reaction, which can greatly reduce the crosslinking density after the bismaleimide is cured and improve the spin of the molecular chain, thereby achieving the toughening effect.

[0034] (2) Since the prepolymer viscosity of the diamine-modified bismaleimide resin is relatively high, the molding time is relatively short, and the processability is poor, diallyl bisphenol A is introduced in the present invention. Diallyl bisphenol A can act as a toughening agent for the bismaleimide resin and also as an active diluent to improve the processability of the system. Compared with the bismaleimide resin modified with only diamine, the viscosity of the system is greatly reduced during the preparation of the casting body, and the molding time is greatly extended.

[0035] (3) Diamine can be reacted with maleic anhydride to synthesize bismaleimide resin. Compared with the synthesis of bismaleimide resin with diamine, the present invention directly uses diamine to modify bismaleimide, omitting the steps of ring-opening reaction and dehydration cyclization of diamine and maleic anhydride, greatly improving the modification efficiency and shortening the process time.

[0036] (4) The present invention has good modification effect on bismaleimide resin, simple process and strong practicality. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is the 1H-NMR chart of the dinitro compound prepared by the present invention.

[0038] Figure 2 It is the 1H-NMR chart of the diamine toughening agent prepared by the present invention.

[0039] Figure 3It is the infrared spectrum of the dinitro compound and diamine toughening agent prepared by the present invention.

[0040] Figure 4 It is the DSC graph of prepolymer B in Example 1-3 prepared in the present invention.

[0041] Figure 5 It is a graph of the impact strength of the unnotched cantilever beam of the experimental samples 1 to 3 of the present invention and the comparative samples 1 to 2.

[0042] Figure 6 It is the TGA graph of experimental samples 1 to 3 of the present invention. DETAILED DESCRIPTION

[0043] The present invention is further described in detail below through specific embodiments, but this should not be construed as limiting the scope of the present invention to the following examples. Without departing from the above-mentioned method concept of the present invention, various substitutions or changes made according to common technical knowledge and conventional means in the art should be included in the scope of the present invention.

[0044] The diamine toughening agent used in the following examples was prepared by the following method:

[0045] ① Preparation of dinitro compounds: 8 g of 2,7-dihydroxynaphthalene, 15.8 g of p-nitrochlorobenzene and 13.8 g of anhydrous potassium carbonate (the molar ratio of 2,7-dihydroxynaphthalene, p-nitrochlorobenzene and anhydrous potassium carbonate is 1:2:2) are reacted at 150°C in 150 mL of N,N-dimethylformamide for 10 hours. After the reaction is completed, it is filtered while hot. After the filtrate is cooled to room temperature, a large amount of crystals are precipitated. The crystals are then filtered and retained. The crystals are washed with water several times and then dried in an oven to obtain dinitro compounds.

[0046] ② Preparation of diamino compounds: 20 g of the prepared dinitro compound was added to 100 mL of ethylene glycol methyl ether under N2 atmosphere, with 25 mL of hydrazine hydrate as a reducing agent, 8 g of activated carbon as an adsorbent, and 1.2 g of FeCl3˙6H2O as a catalyst. The mixture was reacted at 100°C for 8 hours. After the reaction was completed, the mixture was filtered while hot, and the filtrate was evaporated to precipitate a large amount of solid. The precipitated solid was washed with alcohol and water for multiple times and then dried to obtain a diamine toughening agent.

[0047] Example 1

[0048] (1) Preparation of prepolymer A: A diamine toughener and diphenylmethane bismaleimide were mixed in a molar ratio of 1:2, placed in a three-necked flask, and heated in an oil bath with a magnetic stirring device at 180° C. for 20 min to obtain prepolymer A.

[0049] (2) Diphenylmethane bismaleimide and diallyl bisphenol A are added in a molar ratio of 1:0.8, and then prepolymer A is added to form a diamine / bismaleimide / diallyl bisphenol A ternary system. The ternary system is placed in an oven and prepolymerized at a temperature of 140° C. for 1 hour to obtain prepolymer B. The amount of prepolymer A added is 3% of prepolymer B.

[0050] (3) After the prepolymerization, the molten prepolymer B is poured into a mold for vacuum degassing for 1 hour. After the degassing, the curing process is determined according to the DSC curve of the prepolymer B. During the curing process, a step-by-step temperature rise curing process is adopted. The specific curing process is 150°C, 1 hour → 180°C, 2 hours → 210°C, 4 hours → 230°C, 4 hours. The sample obtained after the curing is experimental sample 1.

[0051] Example 2

[0052] (1) Preparation of prepolymer A: diamine toughener and diphenylmethane bismaleimide were mixed at a molar ratio of 1:1.5, placed in a three-necked flask, and heated in an oil bath with a magnetic stirring device at a heating temperature of 180° C. for a prepolymerization time of 20 min to obtain prepolymer A.

[0053] (2) Diphenylmethane bismaleimide and diallyl bisphenol A are added in a molar ratio of 1:0.8, and then prepolymer A is added to form a diamine / bismaleimide / diallyl bisphenol A ternary system. The ternary system is placed in an oven and prepolymerized at a temperature of 150° C. for 1 hour to obtain prepolymer B. The amount of prepolymer A added is 6% of prepolymer B.

[0054] (3) After the prepolymerization, the molten prepolymer B was poured into a mold for vacuum degassing for 0.5 h. After the degassing, the curing process was determined according to the DSC curve of the prepolymer B. During the curing process, a step-by-step temperature increase curing process was adopted. The specific curing process was 150°C, 1h→180°C, 2h→210°C, 4h→230°C, 4h. The sample obtained after the curing was experimental sample 2.

[0055] Example 3

[0056] (1) Preparation of prepolymer A: A diamine toughener and diphenylmethane bismaleimide were mixed in a molar ratio of 1:2, placed in a three-necked flask, and heated in an oil bath with a magnetic stirring device at 180° C. for 20 min to obtain prepolymer A.

[0057] (2) Diphenylmethane bismaleimide and diallyl bisphenol A were added in a molar ratio of 1:0.8, and then 9% of prepolymer A was added to form a diamine / bismaleimide / diallyl bisphenol A ternary system. The ternary system was placed in an oven and prepolymerized at 130°C for 1 hour to obtain prepolymer B. The amount of prepolymer A added was 9% of prepolymer B.

[0058] (3) After the prepolymerization, the molten prepolymer B was poured into a mold for vacuum degassing for 1 hour. After the degassing, the curing process was determined according to the DSC curve of the prepolymer B. During the curing process, a step-by-step temperature increase curing process was adopted. The specific curing process was 150°C, 1 hour → 180°C, 2 hours → 210°C, 4 hours → 230°C, 4 hours. The sample obtained after the curing was experimental sample 3.

[0059] Comparative Example 1

[0060] Diphenylmethane bismaleimide and diallyl bisphenol A were added in a molar ratio of 1:0.8 to prepare a bismaleimide / diallyl bisphenol A binary system. The binary system was placed in an oven and prepolymerized at 140°C for 1 hour to obtain a prepolymer. After the prepolymerization, the molten prepolymer was poured into a mold for vacuum degassing for 1 hour. After the degassing, the curing process was determined according to the DSC curve of the prepolymer B. During the curing process, a step-by-step temperature increase curing process was adopted. The specific curing process was 150°C, 1h→180°C, 2h→210°C, 4h→230°C, 4h. The sample obtained after the curing was the comparative sample 1.

[0061] Comparative Example 2

[0062] In order to study whether the addition of prepolymer A will definitely improve the mechanical properties of bismaleimide resin, the present invention studies a system in which a large amount of prepolymer A is added as a comparative example. That is, the amount of prepolymer A added is changed to 18% of prepolymer B, and other conditions are the same as those in Example 1. The sample obtained after curing is comparative sample 2.

[0063] The impact strength, flexural strength and flexural modulus of the above-mentioned experimental samples 1-3 and comparative samples 1-2 are shown in Table 1.

[0064] Table 1

[0065]

[0066] It can be seen from the experimental samples 1 to 3 and the comparative samples 1 to 2 in Table 1 that when an appropriate amount of toughening agent is added, the bending properties and impact properties of the modified resin can be improved, and the comprehensive mechanical properties of the experimental sample 1 are the best.

[0067] It can be seen from comparison sample 2 and experimental samples 1 to 3 that the addition of prepolymer A does not necessarily improve the mechanical properties of the resin system. During the experiment, it was found that when 18% of prepolymer A was added, the viscosity of the resin system increased significantly during the pouring process, and defects were easily generated during the processing, resulting in a decrease in mechanical properties. This shows that the two toughening agents cannot improve the mechanical properties of the system by adding them in any proportion.

[0068] As attached Figure 1 The 1H-MNR diagram of the dinitro compound in the present invention is shown, and there are five different hydrogen proton resonance absorption peaks in the diagram. The peak at δ=8.28 is the peak of the hydrogen proton at a on the benzene ring. Due to the strong electron-withdrawing effect of the nitro group, the density of the extranuclear electron cloud of the adjacent benzene ring decreases, so the peak of the hydrogen proton at a appears in the lowest field. The peak at δ=7.22 is the peak of the hydrogen proton at b on the benzene ring. Due to the conjugation effect of the electron donation of the ether bond, the peak of the hydrogen proton at b appears in the highest field. The peaks of the hydrogen protons c and d in the naphthalene ring appear at δ=7.68 and 7.38 respectively. Since the e in the naphthalene ring is less affected by the conjugation effect of the electron donation of the ether bond, the peak appears in the lower field. According to 1H-NMR analysis, the synthetic product is consistent with the target product.

[0069] As attached Figure 2 The 1H-MNR diagram of the diamine toughening agent in the present invention is shown, and there are six different resonance absorption peaks of hydrogen protons in the diagram. The peak at δ=5.00 is the peak of the amino group at a. The amino group and the ether bond both have electron-donating conjugation effects, which makes the hydrogen proton peak in the benzene ring connected to the amino group move to the high field direction, but the electron-donating ability of the amino group is greater than that of the ether bond. Therefore, the hydrogen proton at b adjacent to the amino group appears in a higher field (δ=6.61), and the peak at c appears at δ=6.81. The peaks of the hydrogen protons at d, e, and f in the naphthalene ring appear at δ=6.96, δ=7.05, and δ=7.81, respectively. According to 1H-NMR analysis, the synthetic product is consistent with the target product.

[0070] As attached Figure 3 The infrared spectra of the two synthetic products of the present invention are shown in FIG. 1506 cm -1 1337cm -1 The asymmetric and symmetric stretching vibration absorption peaks of nitro (-NO2) are 1233cm -1 The stretching vibration peak of the ether bond (COC) is 3005-3091cm -1 It is a weak peak of stretching vibration of carbon-hydrogen bond (CH) on aromatic ring, 1483cm -1 Compared with the spectrum of dinitro compounds, the asymmetric and symmetric stretching vibration peaks of the nitro group in the spectrum of diamines completely disappeared, and the peak at 3392cm -1 and 3442cm-1 A new amino characteristic absorption peak appeared at the position, and the peaks at other positions remained basically unchanged, indicating that the nitro group in the dinitro compound was successfully reduced to an amino group.

[0071] As attached Figure 4 As shown, the DSC graphs of prepolymer B with three contents of prepolymer A in the present invention, the peak temperature of the cured product did not show obvious change with the addition of toughening agent, the DSC peak temperatures of the three prepolymers appeared at 256.7°C, 256.2°C, and 256.6°C, respectively, and the starting temperature of the curing reaction was slightly advanced with the addition of toughening agent.

[0072] As attached Figure 5 As shown in the figure, it is a bar chart of the impact strength of the unnotched cantilever beam impact of the comparative samples 1 to 2 and the experimental samples 1 to 3 in the present invention. It can be seen that the impact strength of the experimental samples increases first and then decreases with the increase of the diamine content. This is because the longer diamine molecular chain reduces the crosslinking density of the cured product, and the diamine contains flexible ether bonds, which improves the spin of the molecular chain, so the impact strength will increase. However, with the increase of the diamine content, the viscosity of the prepolymer increases, which will lead to a large number of defects in the curing process, thereby reducing the impact strength.

[0073] As attached Figure 6 As shown, it is the TGA graph of experimental samples 1 to 3 in the present invention. The initial thermal decomposition temperatures of experimental samples 1 to 3 are 416.7°C, 420.7°C and 420.0°C, respectively. It can be seen that the three experimental samples have very high thermal decomposition temperatures. With the increase of the content of prepolymer A, the high-temperature residual carbon rate of the experimental samples increases.

Claims

1. A method for preparing a toughened bismaleimide resin, characterized in that: The steps include: (1) mixing a diamine toughening agent and diphenylmethane bismaleimide in proportion and reacting them in a molten state to form a prepolymer A; (2) Prepolymer A, diallyl bisphenol A and diphenylmethane bismaleimide are reacted in a molten state to form prepolymer B.

2. The method for preparing a toughened bismaleimide resin according to claim 1, characterized in that: The steps also include: (3) pouring the prepolymer B into a mold and curing it at high temperature to obtain a bismaleimide resin with good toughness and heat resistance.

3. The method for preparing a toughened bismaleimide resin according to claim 1, characterized in that: The diamine toughening agent has a molecular structure as shown in Formula I:

4. The method for preparing a toughened bismaleimide resin according to claim 1, characterized in that: In step (1), the molar ratio of the diamine toughening agent to the diphenylmethane bismaleimide is 1:(1-2).

5. The method for preparing a toughened bismaleimide resin according to claim 1, characterized in that: The prepolymerization temperature in step (1) is 130-180° C., and the prepolymerization time is 10-30 min.

6. The method for preparing a toughened bismaleimide resin according to claim 1, characterized in that: In step (2), the molar ratio of diphenylmethane bismaleimide to diallyl bisphenol A is 1:(0.8-1), and the added amount of prepolymer A in step (2) is 3-18% of prepolymer B.

7. The method for preparing a toughened bismaleimide resin according to claim 1, characterized in that: The prepolymerization temperature in step (2) is 130-150° C., and the prepolymerization time is 0.5-1 h.

8. The method for preparing a toughened bismaleimide resin according to claim 2, characterized in that: Step (3) After the prepolymer B is poured into the mold, vacuum degassing is performed for 0.5-1h.

9. The method for preparing a toughened bismaleimide resin according to claim 1, characterized in that: The curing described in step (3) adopts a step-by-step temperature curing process, and the specific curing process is 150° C., 1 h→180° C., 2 h→210° C., 4 h→230° C., 4 h.

10. A toughened bismaleimide resin prepared according to the method of any one of claims 1 to 9.

Citation Information

Cited By

  • Preparation method of bismaleimide resin system with high impact toughness

    CN119899378A

  • Preparation method of diamine chain extension toughened bismaleimide resin

    CN119899379A